Studies in historical geography and biblical historiography : presented to Zechariah Kallai - Ḳalai, Zekharyah.; Galil, Gershon.; Weinfeld, Moshe. (Vetus Testamentum, Supplements, 2000)
This book is presented to Professor Zecharia Kallai, one of the leading scholars of Historical Geography of the Bible, by his students and friends. It contains a collection of studies in Historical Geography and Biblical Historiography. The book is divided into three parts: Historical Geography, Biblical History and Historiography, and Texts and Textual Studies. The book is concluded with a list of Kallai's publications. Part one contains articles by Shmuel Ahituv, Aaron Demsky, Volkmar Fritz, Gershon Galil, M. Heltzer, André Lemaire, Zeev Safrai, B. Oded and Joshua Schwartz. Part two contains articles by Yairah Amit, Graeme Auld, David Elgavish, Moshe Garsiel, E.L. Greenstein, A.F. Rainey, Shmuel Vargon. And part three contains articles by Yitzhak Avishur, Bob Becking, Moshe Elat, Bezalel Porten andamp; Ada Yardeni, Moshe Weinfeld and Ze'ev Weisman.